Wounding Response in Relation to Polar Transport of Radiocalcium in Isolated Root Segments of Zea mays - Evans, Evan C. (1966)
A perfusion bridge technique is described which permits the continuous collection of exudations from both ends of corn root segments. By exposing the central portion of the segments to radiocalcium, the amounts and rates of tracer movement in either direction may be determined. Typically, a peak in both acropetal and basipetal transport occurs at about 90 minutes after exposure to tracer. This transport peak is followed by a sharp decline to relatively low transport rates. Thereafter the 2 perfusates from opposite ends of a segment pair show significant differences. The acropetal increments decrease somewhat erratically to 0 at 10 to 12 hours, while the basipetal increments steadily increase to a steady-state value which remains constant from 8 to 24 hours. After a segment pair has reached steady-state polar transport, a fresh cut on the apical ends causes the resumption of acropetal transport. Such response suggests that polar transport in these root segments is at least partially a wound response. A possible explanation of the complex transport behavior is advanced.